2012
DOI: 10.1038/npp.2012.99
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Selecting Between Food and Cocaine Reinforcement are Mediated by Estrogen

Abstract: Cocaine-dependent women, relative to their male counterparts, report shorter cocaine-free periods and report transiting faster from first use to entering treatment for addiction. Similarly, preclinical studies indicate that female rats, particularly those in the estrus phase of their reproductive cycle, show increased operant responding for cocaine under a wide variety of schedules. Making maladaptive choices is a component of drug dependence, and concurrent reinforcement schedules that examine cocaine choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
105
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(129 citation statements)
references
References 54 publications
17
105
4
1
Order By: Relevance
“…Indeed, all else being equal, merely shortening the interchoice interval from 10 to 1 min was sufficient to make rats shift their choice from saccharin to cocaine within one single 30-trial choice session. This setting-specific control of cocaine choices in the same rats and at the same dose of cocaine (ie, 0.25 mg per injection) confirms previous research (Kerstetter et al, 2012) and helps to resolve current discrepancies across cocaine choice studies in rats, as explained in the Introduction Thomsen et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Indeed, all else being equal, merely shortening the interchoice interval from 10 to 1 min was sufficient to make rats shift their choice from saccharin to cocaine within one single 30-trial choice session. This setting-specific control of cocaine choices in the same rats and at the same dose of cocaine (ie, 0.25 mg per injection) confirms previous research (Kerstetter et al, 2012) and helps to resolve current discrepancies across cocaine choice studies in rats, as explained in the Introduction Thomsen et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…This hypothesis is supported by a recent choice study that uniquely manipulated the duration of the interchoice interval while keeping all else equal. As expected, when the interchoice interval was sufficiently shortened to allow the drug influence at the time of choice, most rats shifted from sweet reward to cocaine almost exclusively (Kerstetter et al, 2012).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…In support of this hypothesis, studies have shown that laboratory rodents learn to self-administer cocaine (e.g., Richardson and Roberts 1996;España et al 2010) and associate a specific context with cocaine reward (e.g., Spyraki et al 1982;Vidal-Infer et al 2012) remarkably quickly. The rewarding effects of cocaine are so powerful that a number of studies have shown that an especially addiction-prone subset of laboratory animals trained to selfadminister cocaine prefer cocaine over feeding and mating and compulsively self-administer cocaine at fatal rates (Deneau et al 1969;Lenoir et al 2007;Kerstetter et al 2012;Perry et al 2013). This suggests that the coupling of cocaine's procognitive effects with overstimulation of the reward system may result in dysregulated behavioral outcomes rather than enhancement of behavioral control.…”
Section: Cocainementioning
confidence: 99%